iGestHealth – A self-management integrative review of chemotherapy treatment symptoms - Rafael, Marisa (2021)
Introduction: Many times the cancer patient has to face specific symptoms due to chemotherapy treatments that need to be managed to maintain their quality of life. Therefore, it is foremost important the promotion of skills and knowledge to enable the patient to self-manage their symptoms and complications treatment related and to support the decision making process in healthcare.   Objective: Look into the current scientific knowledge regarding therapeutic guidelines which encourage self-management of the symptoms such as alopecia, skin changes, sexuality and urinary disorders for patients undergoing chemotherapy.   Method: An integrative literature review was conducted on MEDLINE® e CINAHL® databases, creating a review protocol, the research was also extended to grey literature.   Results: From the literature review we selected 9 of 140 articles for alopecia, 14 of 91 articles for skin changes, 13 of 52 articles for sexuality and 4 of 53 articles for urinary disorders. On the search from other information sources 5 documents were selected for alopecia, 8 for skin changes, 5 for sexuality and 7 for urinary disorders.   Conclusions: The development of the therapeutic guidelines for the four symptoms included in this study showed to be a useful tool on the development of skills for the self-management of symptoms experienced during chemotherapy contributing for the patient’s empowerment, assisting the decision making process and also improving their perception of well-being and quality of life.